Tailoring structural properties of lanthanum orthoniobates through an isovalent substitution on the Nb-site. Issue 9 (18th July 2018) - Wachowski, Sebastian; Kamecki, Bartosz; Winiarz, Piotr; Dzierzgowski, Kacper; Mielewczyk-Gryń, Aleksandra; Gazda, Maria
Abstract : The structure and thermomechanical properties of As-substituted lanthanum orthoniobates are presented and an in-depth analysis of a broad range of other substituents is performed. Abstract : A tetragonal polymorph of lanthanum orthoniobate can be stabilized to room temperature by the substitution of Nb with an isovalent element. LaNb1− x As x O4 (0 < x ≤ 0.3), where As is an element stabilizing the tetragonal structure, were successfully synthesized using a combined co-precipitation and solid-state reaction method. The phase transition temperature, above which the material has a tetragonal structure, decreases linearly with increasing As content, and LaNb0.7 As0.3 O4 is tetragonal at room temperature. The analysis of the influence of different isovalent substituents, namely V, Sb and Ta, has shown that there is a relation between the properties of the chemical element and its effect on the structure. It was proposed that the electronegativity of the substituent determines the type of stabilization – the tetragonal/monoclinic structure is stabilized by chemical elements with electronegativity higher/lower than that of niobium. The slope of the phase transition temperature dependence on the substituent content has been proposed as a parameter determining the "quality" of the stabilization, since a steeper function leads to a larger decrease of transition temperature for the same content of different substituents. The analysis has shown that apart from the electronegativity, the stabilization of the tetragonal structure depends also on the ionic radius of a substituent. Arsenic has been found to be a better stabilizer of the tetragonal polymorph of lanthanum orthoniobate than Sb, but worse than V.